Interrogating Technology‐led Experiments in Sustainability Governance. Issue 4 (27th May 2020) - Bernards, Nick; Campbell‐Verduyn, Malcolm; Rodima‐Taylor, Daivi; Duberry, Jerome; DuPont, Quinn; Dimmelmeier, Andreas; Huetten, Moritz; Mahrenbach, Laura C.; Porter, Tony; Reinsberg, Bernhard
Abstract: Solutions to global sustainability challenges are increasingly technology‐intensive. Yet, technologies are neither developed nor applied to governance problems in a socio‐political vacuum. Despite aspirations to provide novel solutions to current sustainability governance challenges, many technology‐centred projects, pilots and plans remain implicated in longer‐standing global governance trends shaping the possibilities for success in often under‐recognized ways. This article identifies three overlapping contexts within which technology‐led efforts to address sustainability challenges are evolving, highlighting the growing roles of: (1) private actors; (2) experimentalism; and (3) informality. The confluence of these interconnected trends illuminates an important yet often under‐recognized paradox: that the use of technology in multi‐stakeholder initiatives tends to reduce rather than expand the set of actors, enhancing instead of reducing challenges to participation and transparency, and reinforcing rather than transforming existing forms of power relations. Without recognizing and attempting to address these limits, technology‐led multi‐stakeholder initiatives will remain less effective in addressing the complexity and uncertainty surrounding global sustainability governance. We provide pathways for interrogating the ways that novel technologies are being harnessed to address long‐standing global sustainability issues in manners that foreground key ethical, social and political considerations and the contexts in which they are evolving. Abstract : In the current environments of high complexity and uncertainty surrounding sustainable governance initiatives, we argue that ethical, social and political considerations should be given foremost priority.